2007
DOI: 10.1007/s11630-007-0001-x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigations of micro air injection to control rotating stall

Abstract: Steady discrete micro air injection at the tip region in front of the first compressor rotor has been proved to be an effective method to delay the inception of rotating stall in a low speed axial compressor. Considering the practical application a new type of micro injector was designed and described in this paper, which was imbedded in the casing and could be moved along the chord. In order to verify its feasibility to other cases, such as high subsonic axial compressor or centrifugal compressor, some other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…The injection results in the reduced strength of the vortex oscillations, smaller vortices, and reduced total pressure loss. In an axial compressor, the optimum location for the injection is at the rotor blade leading edge, or upstream of it [170,176] and an injector throat height lower than four times the rotor tip clearance is recommended [170]. In this optimum location, the injection acts on the tip leakage flow delaying the onset of stall.…”
Section: Injection Suction and Recirculationmentioning
confidence: 99%
See 3 more Smart Citations
“…The injection results in the reduced strength of the vortex oscillations, smaller vortices, and reduced total pressure loss. In an axial compressor, the optimum location for the injection is at the rotor blade leading edge, or upstream of it [170,176] and an injector throat height lower than four times the rotor tip clearance is recommended [170]. In this optimum location, the injection acts on the tip leakage flow delaying the onset of stall.…”
Section: Injection Suction and Recirculationmentioning
confidence: 99%
“…. +1.5% +20% [200] 2012 Injection nozzle CC 2-11% ±0% +20% [176] 2007 Injection nozzle AC 0.15% +9% [176] 2007 Injection nozzle CC 0.9% +10% [201] 2005 Injection nozzle CC 0.9-4.6% ±0% ±0% [202] 2004 Injection nozzle CC 0.5% +25% [178] 2003 Injection nozzle CC 0.9% −1% +15% [178] 2003 Bleed control tube CC −5.5% +56%…”
Section: Injection Suction and Recirculationmentioning
confidence: 99%
See 2 more Smart Citations
“…When the injector is moved away from the impeller blades leading edge, the pressure losses are decreased but the surge margin is decreased also. Nie et al [8] made an experimental investigation about using air injection in a high speed centrifugal compressor. Results showed that the best location to inject air is at the upstream of the impeller blades tip because the flow separation is better controlled and minimized at the impeller inlet.…”
Section: Introductionmentioning
confidence: 99%